Dynamic Patterns and Predominance of Respiratory Pathogens Post-COVID-19: Insights from a Two-Year Analysis - Salma AlBahrani; Samira Jamaan AlZahrani; Thekra N. Al-Maqati; Atheer Almehbash; Anfal Alshammari; Refan Bujlai; Sarah Ba Taweel; Fares Almasabi; Abdullah AlAmari; Jaffar A. Al-Tawfiq (Springer, 2024)
Abstract Introduction Respiratory tract infections (RTIs) stand out as the most frequent causes leading to visits to the emergency department and hospitalizations. This study aims to assess the types and prevalence of respiratory infections across two years following the end of the COVID-19 pandemic. Methods Patients presenting with an influenza-like illness (ILI) were tested using multiplex RT-PCR (QIAstat-Dx, Qiagen). The multiplexed RT- PCR test detects 21 respiratory viruses and bacteria. Results During the study period, PCR test was done on a total of 1,790 samples were tested, and 712 (40%) were positive for a total of 796 pathogens. The mean age (± SD) of the participants was 20.1 ± 28.4 years in 2022 and 21.9 ± 27.6 years in 2023. Among the detected pathogens, the most prevalent were Rhinovirus/Enterovirus 222 (12.4%), followed by RSV A&B (103 cases, 5.7%), and H1N1 Influenza (77 cases, 4.3%). Additionally,  Influenza A/B constituted 172 (9.6%) while parainfluenza constituted (58, 3.2%). SARS-CoV-2 was identified in 3.97% of the samples. Over the two-year period, the monthly pattern of the identified pathogens exhibited fluctuations in the prevalence. Furthermore, variations were observed in the detected pathogens across different age groups. Conclusion In addition to adding significant knowledge to the field of respiratory viral infections, this study emphasizes the necessity of ongoing research and surveillance for the detection and characterization of respiratory viruses, particularly those with the potential for emergence. Such studies would also require setting up a strategy for genotyping and/or sequencing of viruses.